TYPIFICATION OF TECTARIA PARADOXA (POLYPODIACEAE SUB-FAM. TECTARIOIDEAE) - Mazumdar, Jaideep (Research Center for Biology, 2017)
MAZUMDAR, J. 2017. Typification of Tectaria paradoxa (Polypodiaceae subfam. Tectarioideae). Reinwardtia 16(2): 93-95. â Aspidium paradoxum has not yet been lectotypified, because the original material is ambiguous. A specimen from the collections of A. FÃ©e, the author of the species, was located in the herbarium of Montpellier (MPU), which is here designated as the lectotype for this species. It is now known as Tectaria paradoxa, a fern species widely distributed across tropical Asia.